Stereographs of the Spanish-American War, the Philippine American War, the Boer War and World War I - Carson, Marian S.; Kilburn, B. W.; Rau, William Herman (1898)
Photographs from various publishers primarily document the Spanish-American war with emphasis on naval aspect of the war. These images depict the American ship "Terror;" Admiral Dewey's frigate, "Olympia;" the battleships "Oregon" and "Indiana;" gunners on the battleship "Oregon;" sailors from the "Olympia" in a parade after the war ended in December 1898; the wreckage of the American ships "Maine" and "Merrimac" and the destroyed Spanish ship, "Vizcaya." Other images related to the Spanish American War show homefront mobilization in Georgia and Tennessee and views of a fort and occupation depot in Cuba. The LOT also includes one stereograph of the Boer War showing troops preparing to march into the Orange Free State and a stereograph of casualties in a hospital on the Philippine Islands during the Philippine American War. Also includes two Keystone views related to World War II showing the battleship Louisiana at New York harbor and the wreck of a German aircraft in the Oise District, France.
Some caption information appears on recto or verso of stereographs.
Publishers within the LOT: B.W. Kilburn; William H. Rau; Keystone View Company; Strohmeyer & Wyman; and American Stereoscopic Company.
LOT title devised by Library staff.
Captions available on most stereograph mounts.
Keywords: Spanish-American War, 1898 -- Military mobilization -- American; Spanish-American War, 1898 -- Naval operations; World War, 1914-1918.; South African War, 1899-1902.; Naval warfare; Warships; Warships